Management of trauma to the anterior segment of the maxilla: alveolar fracture and primary incisors crown and root fracture - Khalaf , Muna S; Khalaf , Bayan S; Abass , Shorouq M (Journal of Baghdad College of Dentistry, 2021)
Background: An injury to both the primary and permanent teeth and the supporting structures is one of the most common dental problems seen in children. Splinting is usually difficult or impossible to perform in the primary dentition (due to diminutive room size and lack of patient cooperation). Healing must, therefore, occur despite mobility at the fracture line, usually resulting in interposition of connective tissue. In some instances, infection will occur in the coronal pulp. The present study reported a case of trauma to the anterior primary teeth and alveolar bone in a four year old child. The trauma has caused fracture to the crowns and roots of the primary anterior teeth. The following case was managed in a procedure that may provide primary teeth subjected to trauma a better chance than extraction with a better prognosis. Case presentation: a 4 and a half year old child was subjected to trauma in anterior segment of maxilla. Suturing of the torn soft tissue was the first step followed by pulpotomy for the left primary lateral incisor. Fixation of the right primary central and lateral incisors was done by acid etch wire fixation. Both clinical and radiographic follow up was carried out for 6.4 years. Results: healing of the soft tissue was observed after one week and completed after two months. Fixation of the teeth continued for ten months. The fracture lines in the roots remained in position. Clinically there was no sign of any pulpal inflammation or necrosis. Radiographically, no signs of infection to the surrounding tissues could be seen, no resorption in the alveolar bone, external or internal resorption of the root did not happen also. After ten months fixation ended and the wire was removed. At that time there was normal resorption of the roots of the primary incisors in relation with the normal development of the permanent incisors. After 3 years both permanent central incisors erupted in their normal position. After 6.4 years all four permanent incisors erupted into occlusion in their normal position. Conclusion: primary teeth with root fractures and severely mobile coronal fragments can be treated by a conservative approach. The severity of the sequels is directly related to the degree of permanent tooth formation (child’s age), type of dental trauma and extent of the impact.